Board Diversity and Financial Instrument Risk Disclosure of Deposit Money Banks in Nigeria - Chamo, Muhammad Adamu; Kantudu, Aliyu Suleiman; Isa, Muhammad Aminu (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
The study examines the relationship between board diversity and financial instrument risk disclosure (FIRD) of listed deposit money banks in Nigeria. The study employed a descriptive and explanatory research design and the data were generated from annual reports and accounts of sampled firms. Descriptive statistics and regression analysis were used in the data analysis. The study finds that the presence of female directors on boards does not have a significant impact on Financial Institution Risk Disclosure (FIRD) in the banking sector. This may be attributed to specific factors inherent to the sector, as female directors may lack the necessary insights to effectively influence risk disclosure in this context. Additionally, the study concludes that the presence of foreign directors does not significantly affect the FIRD of deposit money banks in Nigeria. This lack of impact may be due to their unfamiliarity with the regional and ethnic dynamics of the Nigerian banking sector. The study recommends incorporating a broader range of board attributes to better assess their influence on FIRD within deposit money banks. Furthermore, it suggests the introduction of a moderating variable that could significantly interact with and affect this relationship.